2006
DOI: 10.1248/cpb.54.522
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-Tagged Shiga Toxin B Subunit Binding Assay: Simple and Specific Determination of Gb3 Content in Mammalian Cells

Abstract: The recombinant 1B-His, in which 6 histidine residues were added at the carboxy termini of the B subunits, was prepared as described previously.15) The BL21DE cells expressing 1B-His were cultured in 300 ml of LB broth (Difco laboratories, Detroit, MI, U.S.A.) supplemented with 50 mg/ml kanamycin (Nacalai Tesque, Inc., Kyoto, Japan) at 37°C for 2 h. The cells were subsequently treated with 1.0 mmol/l isopropyl b-D(Ϫ)thiogalactopyranoside (Wako Pure Chemical Industries, Ltd., Osaka, Japan) at 37°C for 4 h. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Approximately 5 g of each organ from 20-week-old Gla tm Tg(CAG-A4GALT) mice was collected and transferred to Oita University for Gb3 extraction. The organs were homogenized in H2O, glycosphingolipids were isolated and purified by solvent extraction and mild alkaline treatment, and Gb3 was purified by Iatrobeads column chromatography, as previously described (23).…”
Section: Purification Of Mouse Organ Gb3mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 5 g of each organ from 20-week-old Gla tm Tg(CAG-A4GALT) mice was collected and transferred to Oita University for Gb3 extraction. The organs were homogenized in H2O, glycosphingolipids were isolated and purified by solvent extraction and mild alkaline treatment, and Gb3 was purified by Iatrobeads column chromatography, as previously described (23).…”
Section: Purification Of Mouse Organ Gb3mentioning
confidence: 99%
“…Metabolomic studies focusing on the Gb3 structure (18,19) also identified Gb3 isoforms (Gb3 containing various fatty acids without sphingosine modifications) and Gb3 analogs (Gb3 with various sphingosine modifications) in the plasma and urine of patients with Fabry disease. These variations in sphingosine and fatty acid moieties contribute to the structural heterogeneity of Gb3. Several assays for Gb3 determination have been previously described, such as highperformance liquid chromatography (HPLC) of benzoyl-derivatives (20), thin layer chromatography (TLC)-orcinol staining (21), and Shiga toxin B subunit binding assays (22,23); however, recently, Gb3 analysis was performed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) because of its high specificity and sensitivity (13). Gb3 concentrations in the plasma of patients with Fabry disease are often assayed by measuring the ten most abundant Gb3 isoforms (13,24); however, Manwaring et al (19) described the presence of >24 Gb3 isoforms/analogs in the plasma of these patients.…”
mentioning
confidence: 99%
“…The Stx1B binding assay was performed as described previously (23), with some modifications. After glycosphingolipids were separated by TLC as described above, a TLC plate was sunk in a 0.4% polyisobutylmethacrylate (GlycoTech, Rockville, MD, USA) solution (2.5% polyisobutylmethacrylate in chloroform was diluted to 0.4% with hexane) and then blocked with 1% bovine serum albumin in PBS (BSA-PBS).…”
Section: Binding Assaymentioning
confidence: 99%
“…Glycosphingolipids were visualized by spraying orcinol-sulfuric acid reagent for 5-10 min at 100 o C as previously described (32).…”
Section: High-performance Thin-layer Chromatography (Hptlc)mentioning
confidence: 99%
“…The content of Gb3 in the HLCC lines was determined via 1B-His binding assay, as described in our previous study [32]. In order to determine Gb4 content, TLC analysis was conducted quantitatively with TLC plates using a solvent system of chloroform-methanol-water (60:35:8, v/v/v).…”
Section: Quantification Of Gb3 and Gb4mentioning
confidence: 99%